PENGARUH HARGA, COD, GRATIS ONGKOS PENGIRIMAN, REVIEW POSITIF, DAN STATUS VERIFIKASI TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACE (Studi Kasus Pada Mahasiswa FEB UB Saat Pandemi Covid-19) - Abdullah, Luqman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The Covid-19 pandemic have changed consumer’s behavior, from face-to-face purchasing to online shopping. During the pandemic, there were students of Faculty of Economics and Business of Universitas Brawijaya whoprefer shopping via marketplaces, but they were disappointed because the goods were not like what they hadexpected or they were damaged. However, they continued to use the marketplaces. The objective of this research is to identify factors influencing the students to shop in marketplaces. This research uses primary data from 100 students as the respondents. The independent variables are price, cash-on-delivery option, freeshipment, positive reviews, and store’s verified status., while the dependent variable is purchase decision. The Spearman’s rank correlation coefficient was used. this study finds that price negatively affects the purchase decision and that cash-on-delivery option, free shipment, positive reviews, and store’s verified status havepositive effects on the decision.